Long‐term outcomes following drug‐eluting stents versus bare metal stents for primary percutaneous coronary intervention: A real‐world analysis of 11, 181 patients from the british columbia cardiac registry. Issue 1 (4th March 2016) - Iqbal, M. Bilal; Nadra, Imad J.; Ding, Lillian; Fung, Anthony; Aymong, Eve; Chan, Albert W.; Hodge, Steven; Robinson, Simon D.; Siega, Anthony Della
Abstract : Background: Drug eluting stents (DES) are associated with reduced risk of restenosis when compared with bare metal stents (BMS). Their use in ST‐elevation myocardial infarction (STEMI) is debated, owing to concerns about stent thrombosis. There are limited real‐world data comparing DES versus BMS in STEMI. We conducted an observational analysis in this setting and rigorously adjusted for treatment selection bias. Methods: We analyzed 11, 181 consecutive patients with acute STEMI who received either DES or BMS during 2008‐2014 in the British Columbia Cardiac Registry. We analyzed target vessel revascularization (TVR) and mortality at 2 years. Results: Multivariable‐adjusted, propensity‐matched and inverse probability‐treatment weighted analyses found DES to be associated with early and late survival up to 2 years but not TVR. However, when adjusting for measured and unmeasured confounders, instrumental variable (IV) analyses demonstrated that DES use was associated with reduced TVR up to 2 years (Δ = −6.7%, 95% CI: −10.0%, −3.4%, P  < 0.001). DES use was not associated with mortality at 1 year (Δ = −2.3%, 95% CI: −5.0%, 0.4%, P  = 0.100) but associated with reduced mortality at 2 years (Δ = −5.4%, 95% CI: −8.3%, −2.5%, P  < 0.001). Stratified IV analyses indicated that this long‐term survival benefit was largely attributable to the second generation DES. Conclusions: In this study of patients with STEMI, when adjusting for measured and unmeasured factors, DES use was associated with reduced TVR and long‐term survival beyond 1 year. This long‐term survival was largely attributable to the second generation DES. These real‐world data are reassuring and support the use of DES for STEMI. © 2016 Wiley Periodicals, Inc.